Genome-wide association study identifies multiple risk loci for chronic lymphocytic leukemia - Berndt, S; Skibola, C; Joseph, V; Camp, N; Nieters, A; Wang, Z; Cozen, W; Monnereau, A; Wang, S; Kelly, R; Lan, Q; Teras, L; et al. (2013)
Genome-wide association studies (GWAS) have previously identified 13 loci associated with risk of chronic lymphocytic leukemia or small lymphocytic lymphoma (CLL). To identify additional CLL susceptibility loci, we conducted the largest meta-analysis for CLL thus far, including four GWAS with a total of 3,100 individuals with CLL (cases) and 7,667 controls. In the meta-analysis, we identified ten independent associated SNPs in nine new loci at 10q23.31 (ACTA2 or FAS (ACTA2/FAS), P = 1.22 × 10-14), 18q21.33 (BCL2, P = 7.76 × 10-11), 11p15.5 (C11orf21, P = 2.15 × 10 -10), 4q25 (LEF1, P = 4.24 × 10-10), 2q33.1 (CASP10 or CASP8 (CASP10/CASP8), P = 2.50 × 10-9), 9p21.3 (CDKN2B-AS1, P = 1.27 × 10-8), 18q21.32 (PMAIP1, P = 2.51 × 10 -8), 15q15.1 (BMF, P = 2.71 × 10-10) and 2p22.2 (QPCT, P = 1.68 × 10-8), as well as an independent signal at an established locus (2q13, ACOXL, P = 2.08 × 10-18). We also found evidence for two additional promising loci below genome-wide significance at 8q22.3 (ODF1, P = 5.40 × 10-8) and 5p15.33 (TERT, P = 1.92 × 10-7). Although further studies are required, the proximity of several of these loci to genes involved in apoptosis suggests a plausible underlying biological mechanism. © 2013 Nature America, Inc. All rights reserved.